A retrospective analysis of COVID-19 positive patients admitted in a tertiary care hospital wards in Mizoram, India - Anusuya, Ganesh Shanmugasundaram; Zuala, Sang; C , Vankhuma; Varte, Zorinsangi; Pachuau, Lalramenga (Asian Journal of Medical Sciences, 2022)
Background: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2. It primarily presents with respiratory symptoms and can result in damage to the digestive, nervous, and cardiovascular systems. The clinical profile of COVID-19 positive patients and factors associated with mortality has not been studied in patients admitted in wards in Mizoram. Aims and Objectives: The aim of the study was to determine the clinical profiles and outcome of the COVID-19 positive patients admitted in wards of Zoram Medical College, Mizoram. Materials and Methods: A descriptive record based cross-sectional study was conducted in Zoram Medical College, Mizoram among 742 COVID-19 positive patients admitted between March 27, 2020, and April 19, 2021. Individuals with confirmed COVID-19 positive by reverse transcriptionpolymerase chain reaction test from nasopharyngeal swabs were included in the study. Patient’s information was collected from the hospital medical record consisting of demographic details, exposure history, comorbidities, etc. Data were analyzed using SPSS 22 version. P<0.05 was taken as statistically significant. Results: The mean age was 40 years and 59.4% were males. Most of the patients (31.40%) had a history of travel and 52.4% were symptomatic. The common symptoms reported were fever (63.75%), cough (49.10%), sore throat (23.39%), and shortness of breath (18.77%). Among those with comorbidities nearly 66.9% had diabetes mellitus, hypertension (48.6%), chronic heart disease (14.2%), and chronic lung disease in (8.1%). The mortality was only 1.8%. In univariate logistic regression analysis, mortality was associated with increased age >60 years (46.15%) [odds ratio [OR]: 21.56; P=0.005], patients having fever (76.92%) [OR: 6.8; P=0.004], and comorbidities (76.92%) [OR: 21.56; P=0.005] as risk factors. Conclusions: Mortality in COVID 19 positive patients admitted in Zoram Medical College, Mizoram was associated with increased age, comorbidities, and patients who were symptomatics.